Container handling using multi-agent architecture. (13th August 2009) - Kefi, Meriam; Ghedira, Khaled; Korbaa, Ouajdi; Yim, Pascal
Container terminals are essential intermodal interfaces in the global transportation network. Efficient container handling at terminals is important in reducing transportation costs and keeping shipping schedules. This paper discusses a multi-agent model to simulate, solve and optimise the amount of storage space for handling container departures within a fluvial or maritime port. The multi-agent model is developed to minimise the expected total number of shifts or relocations while respecting spatio-temporal constraints. Experimental and numerical runs are given and illustrated. These runs carry out the proposed multi-agent model with comparison to the associated centralised version, basing on non-informed search algorithm and informed search algorithm. They show that the multi-agent model reduces rather the number of expected relocation movements especially when basing on informed search algorithm. We have also compare performances of our model with those of the B&B method and the heuristic-based method proposed in related works.